The Ethical and Legal Conundrum: Should a Mother Owe a Duty of Care to her Unborn Child? - Do, Christina; Mapulanga-Hulston, Jackbeth (Curtin Business School, 2013)
It is likely that, for emotional and moral reasons, the vast majority of society would agree with the proposition that a mother ought to care for and protect her unborn child. However, it is questionable whether those same members of society would all agree with the imposition of a broad, legally enforceable duty of care on an expectant mother, when armed with knowledge of the consequences that may flow from breach of such a duty. This research paper seeks to examine the competing international policy considerations in order to conclude whether the imposition of such a duty is appropriate and acceptable in modern Australia. This analysis will compare the approaches to such a duty in Canada and the United Kingdom. Presently in Australia, the circumstances under which a mother owes a duty of care to her unborn child are not settled. The Australian legislature and judiciary are yet to reach a definitive conclusion as to the extent of the duty of care owed by a mother to her unborn child.